2021
DOI: 10.3389/fnut.2021.670289
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 and Folate Levels During Pregnancy and Risk of Gestational Diabetes Mellitus: A Systematic Review and Meta-Analysis

Abstract: Background: The role of vitamin B12 and folate levels with risk of gestational diabetes mellitus (GDM) is unclear. The purpose of the current study was to conduct a systematic review and meta-analysis for assessing the relationship between vitamin B12 and folate concentrations during pregnancy and the risk of GDM.Methods: PubMed, Embase, CENTRAL, and Ovid databases were searched up to 10th December, 2020 for all types of studies assessing the relationship. Qualitative and quantitative analysis of data was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Most notably, genes in the one carbon pool by folate pathway were significantly down-regulated in placentas and umbilical cord bloods, indicating that both pregnant women and fetuses with GDM may have the characteristics of folate deficiency. However, a meta-analysis regarding to the correlation between folic acid and the pathogenesis of GDM provides controversial results [ 57 ]. Larger cohort studies are necessary to explore the correlations.…”
Section: Resultsmentioning
confidence: 99%
“…Most notably, genes in the one carbon pool by folate pathway were significantly down-regulated in placentas and umbilical cord bloods, indicating that both pregnant women and fetuses with GDM may have the characteristics of folate deficiency. However, a meta-analysis regarding to the correlation between folic acid and the pathogenesis of GDM provides controversial results [ 57 ]. Larger cohort studies are necessary to explore the correlations.…”
Section: Resultsmentioning
confidence: 99%
“…For example, lack of available studies, a relatively small number of studies was included in this meta-analysis. Furthermore, the latest meta-analysis indicated that the association between the risk of GDM and vitamin B12 deficiency is conflicting [ 29 ], and the conclusion was derived from descriptive analysis which does not allow to draw safe conclusions. Due to these contradictory results, we conducted this updated analysis that included all published observational studies to clarify the potential link between vitamin B12 levels and imbalance of serum folic acid and vitamin B12 to the risk of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the findings of existing meta-analyses and systematic reviews are contradictory, and the significance of the folic acid/vitamin B12 in the risk of GDM remains unknown. A negative link was detected in 1 systematic review; however, it was based on just two publications with tiny samples [ 28 ]; the other systematic review was irrelevant as it included three completely different studies [ 29 ] and the most recent has shown that higher plasma/serum folic acid may increase GDM risk but with a low grade of quality.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of these two biomarkers were significantly and inversely correlated in our population (r = −0.087, p < 0.05). The ratio of folic acid/vitamin B 12 and GDM risk has been investigated in several studies [ 15 , 16 , 17 ] and analyzed in a meta-analysis [ 47 ]. Nevertheless, these studies have yielded contradictory results with negative, positive and no link detected.…”
Section: Discussionmentioning
confidence: 99%